Maxims of university leadership - Sahol Hamid Abu Bakar (Penerbit Universiti Teknologi Mara, 2012)
This book is a must read for leaders or for those who aspire to become leaders at institutions of higher education. This book shares the author's many years of higher education leadership experience, woven together with a unique blend of anecdotes and powerful kernels of leadership wisdom, tinged with a local flavour. The maxims outlined in this book provide rich insights into the leadership issues at higher education while also providing tried and true details of the "actions" required in handling these issues. The maxims also provide a wide range of perspectives that encompasses the management, associates in leadership, staff, students and stakeholders. Maxims of University Leadership is a simple-to-understand book that supports core values which promote effective leadership behaviours that can create a workforce that is committed and enggaged in realising the vision of the institution and the nation. Campus and faculty leaders would certainly benefit from this practical guide to handling complex issues in higher education leadership.